Penerapan prinsip manajemen kelas dan pengaruhnya terhadap motivasi belajar siswa di sekolah dasar - Pujiman Pujiman; Rukayah Rukayah; Matsuri Matsuri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This study aims to describe the implementation of classroom management principles and explain the impact towards 2nd grade students’ learning motivation in SDIT Alif Smart Surakarta. the participant of this study are 34 students and 2 teachers. Analytical data technique that used in this study is Interactive data analytic. Based on the analytic, concluded that classroom management in SDIT Alif Smart Surakarta implemented properly suitable with the classroom management principles, there are: (1) teacher’s gesture like enthusiastic, warmness, and intimateness. (2) challenging learning. (3) various learning activities. (4) teacher’s suppleness in every actions. (5) positivity instruction on the students. (6) discipline instruction on the students. Through classroom management implementation, students become motivated and indicate behaviors like: (1) active in the class. (2) willing to try difficult things. (3) desire to succeeded learning. (4) willing to start from themselves. (5) survive when facing learning difficulties. (6) pay attention to the teacher. Therefore, the conclusion is classroom management principles affected students’ learning motivation.